Forensic exploration of the mechanical properties of basalt grains in earthenware - Braekmans, Dennis; Broekman, Max J. G. M.; Grashof, Bernd G.; Oudshoorn, Max P. J.; Uittenbroek, Lennard H.; Jacobs, Loe F. H. C. (Equinox Publishing, 2019)
The overall goal of this project is to contribute to reconstruct the innovation mechanisms and development of ceramic production using forensic engineering techniques. Instead of optimizing materials as a driver in modern engineering, here we wish to use these methodologies, but aim to solve questions on advancement in the past fabrication process – and thus ultimately understand the key issues of a less or (un)successful design and subsequent improvement. This paper wishes to address the advantages and constraints regarding to use of basalt in ceramic matrices. By utilizing a standardized set of different test bars comprising different amounts of basalt fired at both 800°C and 1000°C, it can be concluded basalt tempered ceramics have a higher fracture toughness when compared to quartz enriched materials. It is there plausible to identify basalt as a good temper material for (ancient) earthenwares in terms of thermal (shock) activities
Keywords: Experimental Archaeology; Basalt temper; Levant; Fracture Toughness; Ancient ceramics